Ultrasound-Guided Hydroneurolysis of the Median Nerve for Recurrent Carpal Tunnel Syndrome - Fried, Scott M. (Hand (N Y), 2017)
Background: Recurrent carpal tunnel syndrome is often associated with perineural scarring around the median nerve. Surgical options include relatively invasive procedures, such as fat pad grafting, ligament reconstruction, muscle transfer, and nerve wraps. All have limited success because of the possibility of repeated recurrent scarring postoperatively. Methods: We discuss a technique involving injection with external hydroneurolysis of the median nerve under ultrasound guidance for recurrent carpal tunnel. Injection enables a gentler dissection of the surrounding tissues compared with open external neurolysis, with less chance of recurrent scarring. This technique is a unique alternative to repeat operative intervention in recurrent carpal tunnel, as well as a prelude to repeat open decompression and salvage procedures. Results: Ultrasound-guided injection with external hydroneurolysis of the median nerve is a safer, more limited procedure compared with repeat open surgery, usually performed in an office setting. This procedure limits risk, anesthesia, and operating/recovery room expenses, offering relief in 70% to 80% of cases. Furthermore, in the 20% to 30% of patients with inadequate relief, surgery remains a viable option. US provides important information on the anatomy of the median nerve and carpal canal and can rule out covert pathology. Conclusions: We offer an alternative treatment for recurrent carpal tunnel syndrome, a difficult problem for which many surgeons recommend nonoperative treatment. US provides objective data concerning residual nerve compression and allows for dynamic assessment. Theoretically, this also offers a viable solution for surgeons and their patients with recurrent carpal tunnel syndrome before being pressed to consider repeat open surgery.